Resilience and sustainability through nexus planning - Nhamo, L.; Mpandeli, S.; Mabhaudhi, Tafadzwanashe (2023)
Rapid urbanization is placing unprecedented strain on the life-critical resources of water, energy, and food. We need rapid take-up of coordinated (or “nexus”) approaches to urban development and resource management if we’re to make sustainable cities a reality.